Pengaruh Kompleksitas Tugas, Komitmen Organisasi, dan Time Budget Pressure Pada Perilaku Disfungsional Auditor - Widya Krisna Dewi, Ida Ayu; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi, 2019)
The purpose of this study was to examine the effect of auditor dysfunctional behavior caused by task complexity, organizational commitment, and time budget pressure. The location of this study is the BPKP Representative of Bali Province. The population in this study were all Auditor Functional Officers who worked at the BPKP Representative of Bali Province. The sample of this study conducted by saturated sampling techniques. The data used are primary data with data collection technique, namely questionnaires. The data analysis methods used in this study is multiple linear regression analysis. Based on the results of analysis, it is known that task complexity and time budget pressure have a positive effect on auditor dysfunctional behavior while organizational commitment has a negative effect on auditor dysfunctional behavior. Keywords : Task complexity, organizational commitment, time budget pressure, auditor dysfunctional behavior